Evaluation of obtaining activated carbon from wastewater treatment plant sludge in the community of Valencia: a review - Betancurt Romero, Heraldo Manuel (2022)
As the population grows, sewage sludge production will continue to increase due to necessary increase in the number of wastewater treatment plants. This work analyzes studies from recent years on the use of sewage sludge to obtain activated carbon (AC). The results indicate that in 2013 there was a greater scientific production (13,86 %) compared to other years and the country that stands out in the research is China (52,48 %). They also show that 77,23 % of the studies used sewage sludge as the only raw material, and 22,77 % used sewage sludge plus another precursor to improve the adsorption performance of the activated carbons. Removal efficiencies ≥ 50 % were indicated in dyes, organic compounds, chemical compounds and heavy metals (63,6 %, 68,2 %, 71,4 %, 60,6 % respectively), in turn, drugs had a higher percentage (66,7 %) in removal efficiencies < 50 %. In conclusion, there is much interest in recovering sewage sludge, which allows for obtaining a value-added product. The results show high contaminant removal performance, which makes this alternative economically viable.